2020
DOI: 10.1042/bcj20190879
|View full text |Cite
|
Sign up to set email alerts
|

An allosteric hot spot in the tandem-SH2 domain of ZAP-70 regulates T-cell signaling

Abstract: T-cell receptor (TCR) signaling is initiated by recruiting ZAP-70 to the cytosolic part of TCR. ZAP-70, a non-receptor tyrosine kinase, is composed of an N-terminal tandem SH2 (tSH2) domain connected to the C-terminal kinase domain. The ZAP-70 is recruited to the membrane through binding of tSH2 domain and the doubly phosphorylated ITAM motifs of CD3 chains in the TCR complex. Our results show that the tSH2 domain undergoes a biphasic structural transition while binding to the doubly phosphorylated ITAM-ζ1 pep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 75 publications
1
22
0
Order By: Relevance
“…This behavior has been demonstrated for different protein-protein interaction domains. However, despite their critical roles in many important biological pathways, little information is currently available on Src Homology 2 (SH2) domains, for which only little evidence of interdomain allosteric regulations has been reported (Tsutsui et al, 2016;Gangopadhyay et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This behavior has been demonstrated for different protein-protein interaction domains. However, despite their critical roles in many important biological pathways, little information is currently available on Src Homology 2 (SH2) domains, for which only little evidence of interdomain allosteric regulations has been reported (Tsutsui et al, 2016;Gangopadhyay et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting data are in agreement with previous studies that showed that the C-SH2 of ZAP-70 undergoes a large conformational change upon binding of an ITAM and that it is dynamic in the absence of a bound peptide. 19,20 Conversely, we find that the C-SH2 of Syk is relatively rigid, even in the unbound state, and does not undergo a similar conformational rearrangement upon binding a peptide. The bias of the Syk tSH2 module towards a conformation resembling that found in the ON state of the kinase, even in the absence of ITAM peptides, suggests that the auto-inhibited state of Syk is less stable than that of ZAP-70.…”
Section: Introductionmentioning
confidence: 77%
“…allowing the binding pocket of the N-SH2 to be fully formed. 19 Binding of the second phosphorylated tyrosine in this pocket remodels the dynamics of the C-SH2 domain binding pocket, resulting in a higher affinity for the phosphorylated ITAM. We show that the C-SH2 of ZAP-70 is more flexible in the ITAM-free state and binding of a peptide rigidifies this domain.…”
Section: Sequence Differences Between the Zap-70 And Syk Tsh2 Modules Are Conservedmentioning
confidence: 99%
“…Steady-state ligand-binding experiments suggest that the tSH2 domain binds to the doubly phosphorylated ITAM peptides in a biphasic manner [ 179 ]. In the first step, the C-SH2 domain binds uncooperatively to the N-terminal tyrosine phosphate with low nanomolar affinity, subsequently facilitating the formation of the N-SH2 phosphate-binding pocket enabling second phosphotyrosine to bind with micromolar affinity leading to remodeling of C-SH2-binding site.…”
Section: Regulation Of Zap-70 Activationmentioning
confidence: 99%
“…The functional significance of such two-step ligand binding is still not completely understood. Comparison of the apo- and holo- structure of the tSH2 domain revealed that the N-SH2-binding pocket formed at the interface of the tSH2 domains [ 169 , 174 , 179 , 182 ]. A non-covalent network of amino acids residues allosterically couples the tSH2 domains during ligand binding.…”
Section: Regulation Of Zap-70 Activationmentioning
confidence: 99%